Association of exercise participation levels with cardiometabolic health and quality of life in individuals with hepatitis C. Issue 1 (24th March 2021) - Hallsworth, Kate; Gosrani, Shion; Hogg, Sarah; Patel, Preya; Wetten, Aaron; Welton, Rachael; McPherson, Stuart; Campbell, Matthew D
Abstract : Objective: Hepatitis C virus (HCV) infection is associated with an increased risk of cardiovascular disease (CVD) and reduced health-related quality of life (HRQoL). Although physical activity (PA)/exercise has been shown to reduce CVD risk and improve HRQoL in patients with liver disease, there is limited data in HCV. We aimed to explore the association between PA/exercise levels, CVD risk and HRQoL in patients with HCV and assess individuals' attitudes to PA/exercise. Design: Cross-sectional observational study recruiting consecutive patients with HCV from viral hepatitis clinics. Data were collected on CVD risk factors, anthropometry, HRQoL and the Exercise Benefits and Barriers Scale (EBBS). Results: 86 patients were recruited (71% men, 94% white, age 52±13 years); 49% of the cohort self-reported to be currently active. Although HRQoL was reduced across the cohort, patients that were regularly 'active' reported significantly higher HRQoL scores across Short-Form 36v2 domains compared with their inactive counterparts (p<0.05). Metabolic and cardiovascular characteristics were no different between groups stratified by PA/exercise status (p>0.05). EBBS scores were similar in the 'active' versus 'inactive' groups, however, patients categorised as 'active' scored significantly higher on the psychological outlook and social interaction subscales (p<0.05) than those that were 'inactive'. There were significant associations between EBBS scores and HRQoL (p<0.05). Conclusions: PA/exercise is associated with increased HRQoL in patients with HCV irrespective of clinical parameters. Addressing specific motivators/barriers to exercise for patients will be key to designing effective PA/exercise interventions in this patient population to ensure maximum uptake and adherence.